Mainstreaming of emergency contraception pill in India: Challenges and opportunities - Anvita Dixit; M E Khan; Isha Bhatnagar (Wolters Kluwer Medknow Publications, 2015)
Background: Emergency Contraception Pill (ECP) is an essential intervention to prevent unwanted pregnancies. However, its use has remained low due to various barriers including reservations among medical fraternity. Materials and Methods: This paper presents findings on barriers to ECP's easy access for potential users from (i) a cross-sectional survey of providers' attitudes, beliefs, and practices and interviews with key opinion leaders, (ii) three consultations organized by Population Council with policymakers and public health experts, and (iii) evidence from scientific literature. Results: The major barriers to easy access of ECP include misconceptions and reservations of providers (disapproval of ECP provision by CHWs, opposition to its being an OTC product, and myths, misconceptions, and moral judgments about its users) including influential gynecologists. Conclusion: For mainstreaming ECP, the paper recommends educational campaign focusing on gynecologists and CHWs, relaxing restrictive policy on advertisement of ECP, involving press media and strengthening supply chain to ensure its regular supply to ASHA (CHW).